Social inequality, fortified settlements and enclosures in the Southern Iberian Chalcolithic (3rd Millennium BC). An open discussion - Márquez-Romero, José Enrique; Jiménez-Jáimez, Víctor José (Deutsches Archäologisches Institut/Harrassowitz, 2021)
Amongst many Mediterranean archaeologists the idea that the Iberian Peninsula, and especially its southernmost regions, witnessed the rise and development of some of the earliest complex communities in Western European Late Prehistory has become a commonplace. In particular, the Iberian Chalcolithic is predominantly considered a paradigm of early social inequality, a starting point for the emergence of state societies and the decline of kinship as the basis for most human social relationships. This perception is grounded on the scientific results of several research projects undertaken in the last three decades of the 20th century.
The Author shall obtain a digital version of his work 0 years after publication, should he have transferred the corresponding rights for digital editions to the DAI. From such date the Author is free make available a copy of this digital version on a public-access non-profit academic server without any temporal restrictions.
Keywords: Restos arqueológicos prehistóricos; Edad del cobre; Prehistoria; Calcolítico; Iberian Peninsula; Recintos de fosos